Improving Fiqh Learning Achievement on the Sunnah Rawatib Prayer Material Through the Demonstration Method for Class III MIS MA Citeureup Students - Ela Hayati (Jurnal Aghniya, 2023)
Background: The learning achievement of Islamic jurisprudence (Fiqh) students on the topic of sunnah rawatib prayer at MIS MA Citeureup is still low (54.54% completion). This is because conventional lecture learning lacks active student engagement. Demonstrations were chosen to make abstract material concrete, building understanding, skills, and active participation simultaneously. Method: The qualitative-quantitative Classroom Action Research (CAR) took place from June to August 2023. Cycles I, II, and III each consisted of 4–6 meetings. Each cycle included planning, implementation of student-led demonstrations, activity observations, formative tests, and reflection. Data were obtained through observation sheets and test scores (Minimum Completion Criteria 75). Results: Classical completion: Cycle I 68.18% (average 73), Cycle II 86.36% (79.6), Cycle III 90.78% (79.7). The average increased by 22.3 points, and absorption capacity of ≥70 was achieved at 85%. Observations showed increased activity, courage to practice, and the ability to memorize the rak'ah and prayers of the raha'ib prayer. Conclusion: The demonstration method effectively improved the Islamic jurisprudence learning achievement of third-grade students in the Islamic Junior High School (MIS) of Citeureup. It is recommended that Islamic jurisprudence teachers regularly implement it, synergize it with visual media, and increase independent practice at home to maintain the results.